Evaluation of inversion algorithm sensitivity in stratospheric ozone DIAL profile - Orte, F. (2011)
The DIAL system belonging to Observatorio Atmosférico de la Patagonia Austral, Río Gallegos, Argentina has been included in the NDACC since December 2008. One caveat of large networks such as NDACC is the difficulty to report information of similar nature consistently from one research group (or instrument) to another. The inversion algorithm used in the stratospheric ozone DIAL measurements involves different source of systematic and statistic errors. Due to the rapid decrease of the signal-tonoise ratio in the high stratosphere, it is necessary to degrade the vertical resolution of the measurement in order to limit the statistical error at this altitude range, to reasonable values. The final statistical error on the measurement is the result of a compromise between the experimental system characteristics such as the duration of the measurement and the final vertical resolution. The aim of this study is test the DIAL algorithm resolution used to retrieve the ozone profile comparing with the synthetic ozone profile. This synthetic ozone profile is calculated by mean of lidar equation using an ECC sonde profile as input parameter. This ozone profile was measured with an ozonesonde launched in Río Gallegos in March 2011 as part of intercomparison campaign